MENCIPTAKAN KEUNGGULAN BERSAING USAHA KECIL MENENGAH KULINER KOTA BANDUNG - Wa Ode Zusnita Muizu; Anggun Dwi Aprina Guel; Umi Kaltum (PEKBIS, 2018)
The growth of the culinary business continues to experience growth. The numbercontinues to increase from year to year. This situation certainly has an increasinglytight competition level. Especially at this time, where the industry has been movingtowards digitalization, which has caused the challenges of business competition andthe workforce to become more dynamic and changing, which causes almost all ofthe work's character to change as well. character and ability to work. This workability is often referred to as competence. In order to survive in a businessenvironment that is full of dynamics, a business actor needs to master many thingsranging from technical skills, decision making, and human skills. Mastery of thesecompetencies is often ignored by business actors, thus affecting the sustainability oftheir business. The purpose of this research is to study and analyze the competitiveadvantage of UKM in Bandung City Culinary through competence. This researchwas conducted on 114 entrepreneurial UKM UKM respondents in the City ofBandung using descriptive survey method using simple regression analysis. Theresults of data processing concluded that the competence had an effect of 69.4% onthe formation of competitive advantage of SMEs in Bandung City Culinary.